Marfa Flights : Aerial Views of Big Bend Country - Chaplo, Paul V. (Book collections on Project MUSE., 2014)
Take an unforgettable sky excursion over Big Bend with photographer Paul Chaplo as he captures the shapes, textures, and colors of the craggy, weathered landforms people usually see only from the ground-and some places no photographer has gone before. Flying from Marfa, and hanging precariously from the open door of an aircraft, Chaplo shares a hawk's eye view of a fiercely beautiful region, revealing the stark and magnificent landscapes carved by the force of eons of wind and water on the arid, mountainous country along the Rio Grande.